SISTEM INTEGRASI USAHATANI PADI SAWAH DAN TERNAK KERBAU DALAM RANGKA PENGEMBANGAN WILAYAH DI KABUPATEN HUMBANG HASUNDUTAN - Hotden Leonardo Nainggolan; Marlon Sihombing; Tavi Supriana; Ma’ruf Tasfin (Jurnal Agrisep, 2016)
This study was conducted to assess the integrated farming system paddy rice and livestock buffaloes in the framework of regional development in Humbang Hasundutan, with linear regression analysis and descriptive analysis. Based on the results of the study concluded: a) system integration paddy rice farming and buffaloes more efficiently with the R/C ratio 2.4795 compared with non-integration with R/C ratioof 2.1705, b) variable; land area, paddy rice seeds, livestock breeds, animal feed, fertilizer and pesticides, labor, dependent of family, capital of farming, the price of paddy rice systems integration give 96.5% influence on the regional development in Humbang Hasundutan Regency, c) variable land area, animal feed and labor has a positive and significant impact on regional development, d) a variable dependents of family has a negative effect and significant impact to regional development, e) variable capital of farming and price otuput system integration rice paddy and livestock buffaloes have a positive influence and significantly to the regional development in Humbang Hasundutan Regency. Based on the results of the study suggested that the government Humbang Hasundutan: a) provide training to improve the skills of the workforce and the management of systems integration paddy rice and livestock buffaloes that have an impact on increasing the income of farmers and regional development in Humbang Hasundutan, b) should provide seed farming quality and superior to affordable price, c) should optimize counseling for farmers or ranchers on how to farm paddy rice and livestock that is better and more efficient, d) should help farmers to obtain capital farming that is more flexible and is responsible for keeping the stability of output prices of agricultural products so that farmers are motivated to improve their production.